SERVICE MANAGEMENT STRATEGY AND UMRAH SERVICE QUALITY AS DRIVERS OF PILGRIM SATISFACTIONAT PT. DARUL ARQAM PROBOLINGGO - Ridho, Zainur; Rohmatillah, Layli; Filda Nuriah A’yun (Institut Agama Islam Negeri Metro, 2025)
This study examines the service management strategies of PT. Darul Arqam Travel and Tour Kraksaan Probolinggo in enhancing Umrah pilgrims’ satisfaction. Using a qualitative phenomenological approach, data were obtained through observation, interviews, and documentation. The findings indicate that PT. Darul Arqam improves service quality through employee recruitment and training, transparent communication, continuous supervision, and responsive customer service. Despite being a new company, it has successfully built trust and loyalty among pilgrims. Challenges remain, including limited resources, operational complexity, and managing expectations. Strengthening training programs, improving complaint handling, and utilizing digital technology are recommended. Effective service management strategies are essential for improving service quality and increasing pilgrim satisfaction.